2014
DOI: 10.1177/0022034514550716
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally Controlled Microchannels of Periodontal Mimic Scaffolds

Abstract: Physiologic bioengineering of the oral, dental, and craniofacial complex requires optimized geometric organizations of fibrous connective tissues. A computer-designed, fiber-guiding scaffold has been developed to promote tooth-supporting periodontal tissue regeneration and functional restoration despite limited printing resolution for the manufacture of submicron-scaled features. Here, we demonstrate the use of directional freeze-casting techniques to control pore directional angulations and create mimicked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 35 publications
0
66
0
2
Order By: Relevance
“…Nano-HA also resembles the biological apatite due to its ultrafine structure, hence playing a pivotal role in hard tissue replacement [52]. Furthermore, directional freezing process can be employed to assist PDL growth, by controlling the freezing orientation to fabricate sub longitudinal pores with angular similarities to native PDL [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nano-HA also resembles the biological apatite due to its ultrafine structure, hence playing a pivotal role in hard tissue replacement [52]. Furthermore, directional freezing process can be employed to assist PDL growth, by controlling the freezing orientation to fabricate sub longitudinal pores with angular similarities to native PDL [24].…”
Section: Discussionmentioning
confidence: 99%
“…The freezing process can be carried out in a more controlled manner to orient the growth of ice crystals in a particular direction [22,23]. More recently Park et al have used directional freeze-casting with gelatine to mimic topographies with angular similarities of the alveolar crest and natural orientation of periodontal ligaments [24].…”
Section: Introductionmentioning
confidence: 99%
“…Using 3D printing and directional freeze‐casting techniques, a fiber‐guiding hybrid scaffold has been designed to spatiotemporally control the morphogenesis, integration, and functionalization of various tissues . Animal experiments have shown that this customized fiber‐guiding scaffold can accurately adapt to defect sites and thus successfully guide cell/tissue directionality during regeneration and facilitate the formation of a more stable ligament‐ligand complex with a rapidly maturing matrix .…”
Section: Periodontal Tissue Engineering Via In Vitro Cell‐materials Dementioning
confidence: 99%
“…More recently, a similar “3D‐patterned, periodontal mimic multiphasic architecture” approach was reported, taking his technology one step closer to clinical translation . The aforementioned fiber‐guiding scaffold has been approved by the U.S. Food and Drug Administration for clinical use . Collectively, 3D‐patterned multiphasic complexes have enabled the reconstruction of periodontal complex architectures for periodontal tissue engineering strategies, but when translated to clinical use, the complexity of tissue‐engineered constructs must be kept to a minimum to ensure cost‐effectiveness and ease of production.…”
Section: Periodontal Tissue Engineering Via In Vitro Cell‐materials Dementioning
confidence: 99%
“…( b ) Periodontal ligament (PDL), alveolar bone (AB), gingiva (G), inferior alveolar artery (IAA), Volkmann’s canals (VC) [22,23]. …”
Section: Introductionmentioning
confidence: 99%